Dexamethasone for delayed edema after intracerebral hemorrhage： To be or not to be? - Yongqing Ye; Jin Xu; Yuhan Han (Heliyon, 2023)
The pathogenesis of delayed cerebral edema after intracerebral hemorrhage is still unclear. In this case report, we speculate that the formation of subdural effusion or hemorrhage is associated with delayed cerebral edema. By referring to the treatment plan of chronic subdural hematoma, adding dexamethasone to routine medication, certain therapeutic effect has been achieved. Dexamethasone may maintain the stability of blood-brain barrier by directly increasing the expression of ZO-1, and reduce the neuroinflammatory response caused by NF-κB pathway by upregulating KLF2 expression, ultimately reducing nerve injury through multiple pathways.